Autoeficacia y procrastinación académica en estudiantes de la Universidad Estatal de Bolívar. Guaranda, 2022 - Ocaña Alvarado, Cinthya Nicole (2022)
ABSTRACT: The objective of this research was to analyze self-efficacy and academic procrastination in students of the University of Bolívar, Guaranda. The population was composed by 415 students of the Social Communication career, from which 200 were considered, through a simple random probabilistic sampling. The research has a quantitative approach, with a cross-sectional, bibliographic and field design, with a descriptive level. The instruments used were the Juan Bendezú Huapaya Self-Efficacy Scale (SS), which evaluates the level of self-efficacy, and the Busko Academic Procrastination Scale (APS) adapted by Álvarez, focused on measuring the tendency to academic procrastination. The data obtained were processed in the SPSS 25.00 IMB software, obtaining as significant results that 62% of the students present a medium level of self-efficacy, and 58.5% exhibit a moderate level of academic procrastination. The results in relation to self-efficacy show difficulties in self-assessment capacity, a partial level of confidence in their abilities, motivation and persistence; regarding to academic procrastination, it is observed the presence of certain procrastination behaviors in academic activities, shortcomings in the use of learning strategies and time management, as well as difficulties in self-regulation. Based on this, an intervention plan focused on strengthening self-efficacy and managing academic procrastination has been developed.